Silica gel as a sorbent and catalyst support: Improvement of technologies and search for alternative production routes - Mamontov, Grigory V.; Evdokimova, E. V.; Saveleva, Anna S.; Zubkov, Alexander V.; Mikheeva, Natalia N.; Mazov, Ilya N.; Knyazev, Alexey S. 1978- (Catalysis in industry)
Silica gels are porous materials that are commonly used both in industry and in everyday life. Russian manufacturers produce spherical and powdered silica gels; however, a number of fields of application of silica gels are entirely dependent on import. Therefore, it is necessary to develop silica gel production technologies, the introduction of which would make it possible to replace imported silica gels. Methods for improving the properties of spherical silica gels and new solutions for the production of SiO2, in particular, silica gel powders and silica gels with an ordered pore structure, are described. It is proposed that they should be produced using cheap feedstocks, in particular, the aluminum industry waste Si-stoff and the cheap natural material diatomite. It is shown that control of the silica precipitation and structure formation parameters provides the formation of silica gels with a wide range of pore structure characteristics, which makes it possible to use them in various fields.